A Journey of Doing Research “In a Good Way”: Partnership, Ceremony, and Reflections Contributing to the Care and Wellbeing of Indigenous Women Living with HIV in Canada - Peltier, Doris; Martin, Carrie; Masching, Renée; Standup, Mike; Cardinal, Claudette; Nicholson, Valerie; Kazemi, Mina; Kaida, Angela; Warren, Laura; Jaworsky, Denise; Gervais, Laverne; de Pokomandy, Alexandra; et al. (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2020)
The relationship between the First Peoples of Canada and researchers is changing as processes of self-determination and reconciliation are increasingly implemented. We used storytelling and ceremony to describe a historic event, the Indigenous Women’s Data Transfer Ceremony, where quantitative data of 318 Indigenous women living with HIV were transferred to Indigenous academic and community leaders. Relationship building, working together with a common vision, the Ceremony, and the subsequent activities were summarized as a journey of two boats. The Truth and Reconciliation Commission of Canada's Calls to Action and Indigenous ethical principles were central to the process. The article ends with team members’ reflections and the importance of shifting power to Indigenous Peoples in regard to data collection, their stories, and the resulting policies.